The messiness of co-produced research with gatekeepers of resettled refugee communities. Issue 3 (1st September 2020) - Gibbes, Cerian; Skop, Emily
ABSTRACT: Co-production of knowledge is identified by researchers and policy-makers as central to the advancement of scientific endeavors to address societal challenges, and as a process of empowerment which improves linkages between theory, knowledge, and action. We reflect on a nascent project we are developing that takes seriously the idea of co-producing knowledge and questions what the "co-" really means in the research development process, particularly with regard to research goals, sites, methods, and funding? Our interdisciplinary project investigates socio-ecological resilience and recovery in urban farms led by refugees, and integrates co-production from the inception of the project through a research collaboration with researchers, practitioners, and refugees involved in the International Rescue Committee's New Roots Program. Through an exploration of the messiness that becomes manifest as the co-production process unfolds, especially the on-the-ground power dynamics that come with forming relationships with resettlement agency gatekeepers, this paper questions the often-idealized notion that co-production, and emergent methodologies, yields win-win situations. Rather, we posit that co-production incurs tentative alliances and significant trade-offs. So, while we embrace the theory behind co-production, we conclude that the key role of gatekeepers means that theory and reality collide as power hierarchies emerge and the process unfolds.